The Rise and Fall of Physiological Theories of the Control of Human Eating Behavior - Levitsky, David A.; Barre, Laura; Michael, John Jeshurun; Zhong, Yingyi; He, Yitong; Mizia, Alyse; Kaila, Sahib (Frontiers in Nutrition, 2022)
Kuhns was the first to suggest that theories in science do not develop in small increments but rather in major leaps to paradigms that examine the same question through very different perspectives. Theories on the mechanism responsible for control of human food intake fall into Kuhn’s description. This article describes how the two major theories of the control of food intake in humans, the Glucostatic Theory, and the Lipostatic Theory, showed initial promise as explanations, but later deteriorated with the slow accumulation experimental data. The locus of theories considered eating behavior as a part of physiological system that regulates the storage of energy on the body. We challenge this fundamental belief with data which suggests that we must be ready to accept a major change in the way we think about eating behavior if we are ever to decrease the prevalence of obesity.